2019
DOI: 10.1111/echo.14365
|View full text |Cite
|
Sign up to set email alerts
|

Role of left ventricle deformation analysis in stress echocardiography for significant coronary artery disease detection: A diagnostic study meta‐analysis

Abstract: Background We compared the diagnostic accuracy of longitudinal strain (LS) imaging during stress echocardiography with visual assessment of wall motion (WM) for detecting significant coronary artery disease (CAD). Methods Our systematic search included studies reporting diagnostic measures for LS imaging and visual assessment of WM for detecting significant CAD during stress echocardiography. Summary diagnostic accuracy measures including area under the curve (AUC), sensitivity, specificity, diagnostic odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
(86 reference statements)
0
5
0
4
Order By: Relevance
“…В недавно опубликованном мета-анализе K. Gupta и соавт. [25] показано, что анализ деформации миокарда во время стресс-ЭхоКГ выполним и обладает более высокой диагностической точностью для выявления клинически значимой ИБС по сравнению с визуальной оценкой только НЛС. По нашим данным, в группе пациентов с выраженным стенозом КА наблюдалось снижение ГПСД ЛЖ по сравнению с исходной, хотя оно и не достигало статистической значимости (17,8±2,8 в сравнении с 15,9±4,6 %; р=0,15).…”
Section: материал и методыunclassified
See 2 more Smart Citations
“…В недавно опубликованном мета-анализе K. Gupta и соавт. [25] показано, что анализ деформации миокарда во время стресс-ЭхоКГ выполним и обладает более высокой диагностической точностью для выявления клинически значимой ИБС по сравнению с визуальной оценкой только НЛС. По нашим данным, в группе пациентов с выраженным стенозом КА наблюдалось снижение ГПСД ЛЖ по сравнению с исходной, хотя оно и не достигало статистической значимости (17,8±2,8 в сравнении с 15,9±4,6 %; р=0,15).…”
Section: материал и методыunclassified
“…[11], так и по данным мета-анализа K. Gupta и соавт. [25], были выше, чем полученные нами. Вероятно, это обусловлено особенностями стресс-ЭхоКГ с использованием тредмил-теста, а именно тем, что регистрация данных для расчета ГПСД ЛЖ при этом виде нагрузки проводится сразу после прекращения пробы, а не на пике нагрузки, как это выполнялось в исследовании M. J. Mansour и соавт.…”
Section: материал и методыunclassified
See 1 more Smart Citation
“…The assessment of regional strain can also be useful in apical and middle segments, since not all segments were created equal. This can be done not only by visual estimation but also with deformation imaging [ 23 , 24 ]. Most importantly, the state-of-the-art ABCDE-SE is able to evaluate not only coronary plaque but it can also comprehensively assess patient vulnerabilities by taking advantage of the extraordinary versatility of the technique.…”
Section: Conventional Stress Echocardiography: Strengths and Pitfamentioning
confidence: 99%
“…Recent meta-analysis has demonstrated that use of quantitative measures of left ventricular systolic function, including left ventricular ejection fraction (LVEF) and global longitudinal strain (GLS) may provide similar diagnostic accuracy for CAD on stress echocardiography (SE) as WMS. 3 , 4 However, the benefit of quantitative measurements has not yet been translated in routine clinical practice. This is, in part, because GLS measurement by speckle tracking is less accurate during the tachycardia induced by SE.…”
Section: Introductionmentioning
confidence: 99%